Exploring Adolescent Mothers’ Experiences of Social and Behavioral Change Communication Interventions for Safe Motherhood in Ndola District, Zambia - Kachimba, Juness; Ngoma, Catherine Mubita; Kwaleyela, Concepta (British Journal of Healthcare and Medical Research, 2025)
Introduction: Adolescent motherhood in Zambia is associated with increased maternal and neonatal risks. Social and Behavioral Change Communication (SBCC) interventions aim to promote safe motherhood practices, yet barriers such as social stigma, cultural myths, and limited access to information may hinder their effectiveness. Understanding the lived experiences of adolescent mothers and Maternal and Child Health (MCH) coordinators is critical to improving SBCC delivery and maternal health outcomes. Aim: To explore the lived experiences of adolescent mothers and MCH coordinators regarding SBCC interventions and their influence on safe motherhood in Ndola District, Zambia. Methods: A descriptive phenomenological study was conducted in 24 urban health centres. Two focus group discussions per centre with 6–10 adolescent mothers each (total n=306) and in-depth interviews with one MCH coordinator per facility (n=24) were conducted. Purposive sampling, audio-recorded sessions, transcription, NVivo coding, and thematic analysis were used to identify key themes. Results: Six major themes emerged from adolescent mothers: (1) perceptions and knowledge of safe motherhood; (2) social and cultural barriers (stigma, myths, fear of judgment); (3) communication and language challenges; (4) facilitators and support systems (trust in health workers, peer and family support, community outreach); (5) preferred interventions and decision-making autonomy; and (6) practical challenges (nutrition, traditional medicine, geographic barriers). MCH coordinators’ perspectives generated five themes: (1) barriers to accessing reproductive health services; (2) facilitators to improve engagement and service access; (3) role of programmatic interventions (service integration, community influencers); (4) decision-making in care (client-centered approach); and (5) perspectives on safe motherhood (education, counseling, and clinical care). Conclusion: SBCC interventions can empower adolescent mothers, improve decision-making autonomy, and enhance maternal health behaviors when participatory, culturally sensitive, and contextually relevant. Recommendations: Strengthen adolescent-friendly services, employ participatory and culturally appropriate SBCC methods, engage families and community leaders, address practical barriers, enhance provider capacity, and integrate SBCC strategies across health and community systems to optimize safe motherhood outcomes.